» Ruine d'estat « Sicherheit in den Debatten der französischen Religionskriege 1557-1589 - Wenzel, Christian (Pariser Historische Studien, 2020)
Security - a category that is as important as neglected when it comes to the French Wars of Religion in the 16th century. Christian Wenzel systematically traces imaginations of security as well as their function in the French Wars of Religion for the first time, with a close focus on the perspective of the historical actors. The present study vividly recounts a broad security debate which influenced the conflicts between 1557 and 1589 to a significant degree. Thereby, the study enables not only new perspectives on pivotal junctions and processes; by introducing "Historical Security Communication" as a heuristic approach, it also contributes to Historical Security Studies and casts a light on the complexity of early modern semantics of security.